Selection, detection and promotion of talented children for Olympic gymnastics: A multidisciplinary experience - Freitas, L. A. G.; Carvalho, F. O.; Oliveira, A. R. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study had the purpose to present a methodology built and tested by a multidisciplinary staff of State University of Londrina, Paraná State, Brazil, to assess, select, detect and promote talented children with potential to expertise in Olympic Gymnastics.